2018
DOI: 10.1002/jemt.23041
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative analysis of the margins of restorations made with different filling resins

Abstract: The evaluation of clinical relevance in this research is crucial to simplify the transfer of knowledge from research by materials engineering into practice in dentistry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Intending to minimize the occurrence of these problems, studies have evaluated the influence of restorative materials and the technique related to cervical margin relocation. It was observed that the type of material used to reallocate the margin had no influence on marginal quality and resistance to fracture after mechanical fatigue [33][34][35].…”
Section: Biomechanical Aspectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Intending to minimize the occurrence of these problems, studies have evaluated the influence of restorative materials and the technique related to cervical margin relocation. It was observed that the type of material used to reallocate the margin had no influence on marginal quality and resistance to fracture after mechanical fatigue [33][34][35].…”
Section: Biomechanical Aspectsmentioning
confidence: 99%
“…As for the insertion techniques of the restorative material, the meticulous stratification with 3 consecutive layers of 1 mm of the restorative material, is capable of presenting marginal quality, but increases the risk of crack formation between the increments [6]; Snowplough technique provides the combined use of a fluid composite resin and one of regular consistency molded together in a non-polymerized state, followed by final polymerization of both materials, which essentially contributes to obtaining a homogeneous tooth-restoration interface and non-porous [21]; and finally, the application of a single layer of fluid bulk fill resin or of regular consistency, which due to its improved curing depth of at least 4 mm, provides a procedure that is easy to perform, fast and with significantly greater surface smoothness [9,35]. Therefore the last two techniques are the ones with more predictable satisfactory results.…”
Section: Biomechanical Aspectsmentioning
confidence: 99%
“…• the marginal integrity and quality of composite fillings [70]. • the effects, in adhesive dentistry, of different drying methods for post space dentin bonding in a direct resin composite core build-up method [71].…”
Section: Dental Treatments and Mineral Tissuesmentioning
confidence: 99%
“…Microstructural investigations made by both optical and scanning electron microscopy (SEM) are recorded in studies using transmission electron microscopy (TEM) to analyze adhesive/root dentin interface [71] and SEM for the quality assessment of composite fillings [70], porosity and size of silk scaffold [108], alginate samples with stem cells [109], and bone substitutes characterization in MFS [111]. SEM analysis with micro-CT was performed to characterize barrier membrane for bone augmentation in dentistry [128] and to study alloy composition of the metallic fixing lamina and microstructure of the deposits on the dental surface [94].…”
Section: Micro-ct Analysis Combined With Other Techniques or Technolomentioning
confidence: 99%
“…This technique allows professionals to insert Bulk Fill resins into the cavity in one single increment of up to 4-5 mm, optimizing the clinical working time [10]. More reactive photoinitiators were incorporated into these composites, which allow greater polymerization depth, and monomers were included, which work as modulators of the polymerization reaction, controlling the stresses, and promoting good bond strength between the tooth structure and the restorative material [11,12]. These changes in composition, may however, be related to the color change of the resins when they come into contact with pigmenting agents.…”
Section: Introductionmentioning
confidence: 99%